Screening and characterization of endophytic bacteria isolated from celery with the potential to promote plant growth - NURIYANAH NURIYANAH; TIWIT WIDOWATI; ANDI MASNANG; LISEU NURJANAH; DAINTY NOVILASARI; SYLVIA J. R. LEKATOMPESSY; RUMELLA SIMARMATA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nuriyanah, Widowati T, Masnang A, Nurjanah L, Novilasari D, Lekatompessy SJR, Simarmata R. 2023. Screening and characterization of endophytic bacteria isolated from celery with the potential to promote plant growth. Biodiversitas 24: 6897-6904. Endophytic bacteria that inhabit plant tissue contribute to the enhancement of host plant growth by producing secondary metabolites. They can improve plant growth by phytohormone modulation and nutrient uptake. In addition, endophytic bacteria can increase plant health and tolerance by antibiotic and hydrolytic enzyme production. This study aims to screen and characterize endophytic bacteria of celery as plant growth promoter agents. Thirty endophytic bacteria were isolated successfully from part of the celery plant using the spread plate and plant piece method which grew at Nutrient Agar media. Based on the characterization assay, 30 isolates may produce IAA with various concentrations of 0.21-7.18 mg/L. In addition, 3 of 30 isolates had phosphate solubilizing activity, in different indexes ranging from 0.71-1.43. Twenty-one isolates were able to grow in an N-free medium, indicating the capability of isolates to fix nitrogen qualitatively. The hydrolytic enzymes assay resulted in 14 amylolytic, 17 proteolytic, and 12 cellulolytic activities. In addition, nine of 30 isolates show multi-activity in amylase, protease, and cellulase enzyme production. Based on the screening results, there are four potential isolates (SLBg 1.2; SLBg 1.5; SLAg 1.1, and SLAg 1.5) as promising plant-growth promoters and were molecularly identified as members of the Bacillus genus. These isolates can be developed as biofertilizers for supporting the cultivation of celery plants.